Fluorescently Labeled DNA Interacts with Competence and Recombination Proteins and Is Integrated and Expressed Following Natural Transformation of Bacillus subtilis - Mirjam Boonstra (American Society for Microbiology, 2018)
ABSTRACT During competence, Bacillus subtilis is able to take up DNA from its environment through the process of transformation. We investigated the ability of B. subtilis to take up fluorescently labeled DNA and found that it is able to take up fluorescein-dUTP-, DyLight 550-dUTP-, and DyLight 650-dUTP-labeled DNA. Transformation with labeled DNA containing an antibiotic cassette resulted in uptake of the labeled DNA and also generated antibiotic-resistant colonies. DNA is primarily taken up at the pole, as it can be seen to colocalize with ComFC, which is a component of the competence machinery. The DNA is taken up rapidly and can be seen to localize with (the actively searching form of) RecA. Colocalization with a homologous locus on the chromosome increases over time. Using microfluidics, we observed replacement of the homologous locus and subsequent expression of the integrated labeled and unlabeled DNA, although whether the integrated DNA contains labeled nucleotides needs to be determined conclusively. Integrated DNA in cells with a doubling time of 60 min is expressed on average 6 h 45 min after the addition of DNA and 4 h 45 min after the addition of fresh medium. We also found that the expression of the incoming DNA under these conditions can occur before cell division and, thus, before complete exit from the competence state. Because the competence machinery is conserved among naturally competent bacteria, this method of labeling is also suitable for studying transformation of other naturally competent bacteria. IMPORTANCE We used DNA that was covalently labeled with fluorescent nucleotides to investigate the transformation process of Bacillus subtilis at the molecular level. We show that the labeled DNA colocalizes with components of the competence machinery, the chromosome, and the recombination protein RecA. Using time-lapse microscopy and microfluidics, we visualized, in real-time, the uptake of fluorescently labeled DNA. We found that under these conditions, cell division is not required for the expression of integrated DNA. Because the competence machinery is conserved in naturally competent bacteria, this method can also be used to investigate the transformation process in many other bacterial species.